Diskriminasi Masyarakat Terhadap Pasien dan Eks Pasien COVID-19 - Yulianti Yulianti; Nikmatul Choyroh Pamungkas (ISJN Journal, 2021)
At the end of 2019 the world arrives with a very dangerous virus, namely the Corona or COVID-19 virus. This virus is a new name given by the World Health Organization for patients with the 2019 corona novel virus infection which was first reported from the city of Wuhan, China. The spread of this virus is very fast and has become a new problem. Because this virus also spread to Indonesia in March 2020. The spread in Indonesia is also very fast and the number of patients continues to increase, so that people are starting to be aware of this virus. Then with a lot of news in the media about the dangers of COVID-19, the public was afraid so that many COVID-19 patients experienced discrimination in society. Patients or ex-patients with COVID-19 receive discrimination in society because of the lack of credible and excessive information obtained from television and online media. So that the public views that patients or ex patients with COVID-19 are easy to transmit the virus and are very dangerous. As for the discrimination that is obtained by labeling, stereotypes, the existence of exclusion because they are considered to still carry the COVID-19 virus. This research method is a descriptive qualitative research method because it is to see in detail the problems faced by patients with COVID-19 or ex patients. The data source of this study used interview data taken from 5 ex COVID-19 patients and supported by literary studies. The results show that there is indeed discrimination experienced by ex COVID-19 patients in the community. Then this discrimination was also experienced by the families of ex COVID-19 patients. Then the social impact faced by ex patients with COVID-19 is due to community discrimination, namely disruption of mental health, reducing social contact with the community, hiding the illness they suffer.